1983
DOI: 10.1530/acta.0.1020068
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation of [35S]methimazole by human and rat lymphocytes

Abstract: The accumulation of 35S labelled methimazole (MMI) was examined in lymphocytes. No uptake of label was found in peripheral blood lymphocytes (PBL) from normal control subjects after in vitro incubation with the drug. Following administration of [35S]MMI to patients with Graves' hyperthyroidism PBL cell to plasma (C/P) 35S activity was greater than 1 in 4 of 11 patients and only in 1 of 7 other patients undergoing thyroidectomy. Thyroid lymphocytes from 2 of these patients showed some accumulation of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…MMI is concen¬ trated by cells in the thyroid (Marchant et al 1972) and salivary glands (Connell et al 1983) as well as by polymorphonuclear leucocytes (Lam & Lindsay 1979). The presence of intracellular peroxidase seems to be important in MMI accumulation (Con¬ nell et al 1983) and lymphocytes, which do not contain peroxidase, do not accumulate MMI (Shewring & Lazarus 1983). We have shown that the immunosuppressive effect of MMI is probably mediated by an action of antigen-presenting cells, such as the monocyte and macrophage, which have a primary role in triggering lymphocyte activation by antigen; in monocytes the drug inhibits oxygen radical generation (Weetman et al 1983a(Weetman et al , 1984b.…”
mentioning
confidence: 99%
“…MMI is concen¬ trated by cells in the thyroid (Marchant et al 1972) and salivary glands (Connell et al 1983) as well as by polymorphonuclear leucocytes (Lam & Lindsay 1979). The presence of intracellular peroxidase seems to be important in MMI accumulation (Con¬ nell et al 1983) and lymphocytes, which do not contain peroxidase, do not accumulate MMI (Shewring & Lazarus 1983). We have shown that the immunosuppressive effect of MMI is probably mediated by an action of antigen-presenting cells, such as the monocyte and macrophage, which have a primary role in triggering lymphocyte activation by antigen; in monocytes the drug inhibits oxygen radical generation (Weetman et al 1983a(Weetman et al , 1984b.…”
mentioning
confidence: 99%